2011
DOI: 10.1016/j.apm.2011.03.042
|View full text |Cite
|
Sign up to set email alerts
|

On channel coordination through revenue-sharing contracts with price and shelf-space dependent demand

Abstract: a b s t r a c tThis paper deals with the problem of coordinating a vertically separated channel under a consignment contract with revenue sharing. We consider the demand of the downstream player, e.g., the retailer, being price and shelf-space sensitive. Under such a setting, the retailer decides on the revenue-sharing percentage and the slotting fee. And the upstream player, e.g., the manufacturer, decides on the retail price and the size of shelf-space. For each item sold, the retailer deducts an agreed-upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 43 publications
(97 reference statements)
0
24
0
1
Order By: Relevance
“…De Giovanni and Roselli (2012) proposed a support programme to remedy the myopically behaved drawbacks in a vendor-buyer channel under such a contractual agreement. Under consignment contracting, the retailer offers the manufacturer a revenue-sharing percentage and the manufacturer responses by setting the stocking quantity and/or retail price (Chen, Cheng, & Chien, 2011;Chen, Cheng, & Lin, 2011;Wang, Jiang, & Shen, 2004). Ours is under the revenue sharing without consignment contracting that is partially motivated by the local government's recycling programmes (Pennsylvania Department of Environmental Protection, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…De Giovanni and Roselli (2012) proposed a support programme to remedy the myopically behaved drawbacks in a vendor-buyer channel under such a contractual agreement. Under consignment contracting, the retailer offers the manufacturer a revenue-sharing percentage and the manufacturer responses by setting the stocking quantity and/or retail price (Chen, Cheng, & Chien, 2011;Chen, Cheng, & Lin, 2011;Wang, Jiang, & Shen, 2004). Ours is under the revenue sharing without consignment contracting that is partially motivated by the local government's recycling programmes (Pennsylvania Department of Environmental Protection, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhou et al [12] adopted the RS contract and quantity discount contract to coordinate a one-manufacturer and one-retailer supply chain in which the demand rate is deterministic and sensitive to the current inventory level. Assuming that demand is affected by the price and shelf-space, Chen et al [13] used the RS contract to coordinate a one-supplier and one-retailer supply chain. In the context of the model developed by Zhou et al [12], Panda [14] assumed that the demand rate is affected by the current inventory level and price and showed that the supply chain cannot be coordinated by the RS contract whereas it can be coordinated perfectly by a revenue-and cost-sharing contract.…”
Section: Revenue-sharing Models In Supply Chain Systemsmentioning
confidence: 99%
“…Then centralized decision-making is applied in section 4.2. This, too, is a common procedure in the supply chain literature (Chen, Cheng, & Chien, 2011;Krishnan, Kapuscinski, & Butz, 2004;Raju & Zhang, 2005;Zhang & Chen, 2013).…”
Section: Modelmentioning
confidence: 99%